Invariant Natural Killer T Cells as Key Players in Host Resistance against Paracoccidioides brasiliensis - Joes Nogueira-Neto; Flavio V. Loures; Alessandra S. Schanoski; David A. G. Andrade; Michelangelo B. Gonzatti; Tania A. Costa; Bruno C. Vivanco; Patrícia Xander; Daniela S. Rosa; Vera L. G. Calich; Alexandre C. Keller (Journal of Immunology Research)
Invariant Natural Killer T (iNKT) cells are key players in the immunity to several pathogens; however, their involvement in the resistance to Paracoccidioides brasiliensis infection remains unknown. Using splenocytes from CD1d (CD1d-/-) and iNKT-deficient (Jα18-/-) mice, we found that iNKT cells are the innate source of IFN-γ after P. brasiliensis infection and are required to potentiate macrophage oxidative burst and control fungal growth. To determine whether iNKT cells contribute in vivo to host resistance against P. brasiliensis infection, we infected intratracheally wild-type and Jα18-/- C57BL/6 mouse strains with the virulent Pb18 isolate. iNKT cell deficiency impaired the airway acute inflammatory response, resulting in decreased airway neutrophilia and reduced IFN-γ, KC, and nitric oxide (NO) production. The deficient innate immune response of Jα18-/- mice to Pb18 infection resulted in increased fungal burden in the lungs and spleen. Besides, the activation of iNKT cells in vivo by administration of the exogenous iNKT ligand α-galactosylceramide (α-GalCer) improved host resistance to P. brasiliensis infection. Although the mechanisms responsible for this phenomenon remain to be clarified, α-GalCer treatment boosted the local inflammatory response and reduced pulmonary fungal burden. In conclusion, our study is the first evidence that iNKT cells are important for the protective immunity to P. brasiliensis infection and their activation by an exogenous ligand is sufficient to improve the host resistance to this fungal infection.